Next Generation Sequencing Reveals Skewing of the T and B Cell Receptor Repertoires in Patients with Wiskott–Aldrich Syndrome - O’Connell, Amy E.; Volpi, Stefano; Dobbs, Kerry; Fiorini, Claudia; Tsitsikov, Erdyni; de Boer, Helen; Barlan, Isil B.; Despotovic, Jenny M.; Espinosa-Rosales, Francisco J.; Hanson, I. Celine; Kanariou, Maria G.; Martínez-Beckerat, Roxana; et al. (Frontiers in Immunology, 2014)
The Wiskott Aldrich syndrome (WAS) is due to mutations of the WAS gene encoding for the cytoskeletal WAS protein (WASp), leading to abnormal downstream signaling from the T cell and B cell antigen receptors (TCR, BCR). We hypothesized that the impaired signaling through the TCR and BCR in WAS would subsequently lead to aberrations in the immune repertoire of WAS patients. Using next generation sequencing, the T cell receptor beta (TRB) and B cell immunoglobulin heavy chain (IGH) repertoires of 8 patients with WAS and 6 controls were sequenced. Clonal expansions were identified within memory CD4+ cells, as well as in total, naïve and memory CD8+ cells from WAS patients. In the B cell compartment, WAS patient IGH repertoires were also clonally expanded and showed skewed usage of IGHV and IGHJ genes, and increased usage of IGHG constant genes, compared with controls. To our knowledge, this is the first study that demonstrates significant abnormalities of the immune repertoire in WAS patients using next generation sequencing.